The Impact of Social Media Marketing, Word of Mouth and Brand Image on Shopee Consumer’s Purchase Intention in Yogyakarta - Sri Harjanti (AIBPM Publisher, 2021)
The research aims to know the Impact of Social Media Marketing, Word of Mouth and Brand Image on Shopee consumer’s purchase intention in Yogyakarta. The method of sample determination uses a non-probability convenience sampling method. An example of this study is that there are 150 Shopee consumers in Yogyakarta. Data collection uses a survey method based on questionnaires. The results show that social media marketing and word-of-mouth have partially affected consumers’ purchasing intentions, while brand image has not. Simultaneously Social Media Marketing, Word of Mouth and Brand Image affect purchase intention of consumers. Suggestions that can be used as input for Shopee are to always pay attention to and strengthen the Word-of-Mouth variable as the most dominant variable in influencing on Shopee consumer’s purchase intention in Yogyakarta, by always maintaining customer satisfaction in using its services.